2020
DOI: 10.1002/bjs5.50290
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of acute diverticulitis with unenhanced low-dose CT

Abstract: Background: The aim of this study was to evaluate the diagnostic accuracy of unenhanced low-dose CT (LDCT) in acute colonic diverticulitis in comparison with contrast-enhanced standard-dose CT (SDCT). Methods: All patients with clinically suspected diverticulitis who underwent LDCT followed by SDCT between January and October 2017 were evaluated prospectively. CT examinations were assessed for signs of diverticulitis, complications and other differential diagnoses by three independent radiologists (two consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
9
0
5
Order By: Relevance
“…However, the evidence is insufficient to recommend it as the first-choice examination. Furthermore, in a recent prospective study on patients with suspected diverticulitis, although unenhanced low-dose CT showed good sensitivity (98.6%) for the detection of diverticulitis with excellent intermodality agreement, it had significantly lower sensitivity (61%) for the detection of complications [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the evidence is insufficient to recommend it as the first-choice examination. Furthermore, in a recent prospective study on patients with suspected diverticulitis, although unenhanced low-dose CT showed good sensitivity (98.6%) for the detection of diverticulitis with excellent intermodality agreement, it had significantly lower sensitivity (61%) for the detection of complications [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the clinical indications (e.g. bowel obstruction, acute appendicitis, diverticulitis and hollow viscus perforation) for an abdominal CT can be addressed with sufficiently high accuracy on NCCT 3,4 . We have also opted to perform abdominal and chest CTs for minor trauma without ICM.…”
Section: Strategies To Conserve Icmmentioning
confidence: 99%
“…However, it can be advantageous in patients with chronic diverticulitis, especially for visualizing a fistula tract ( 29 ). Although low radiation-dose CT without intravenous contrast has a high sensitivity for diverticulitis, smaller perforations and small pericolic or intramural abscesses can be missed using this technique ( 30 ). Therefore, a full-dose CT protocol with intravenous contrast is recommended for patients with suspected acute diverticulitis.…”
Section: Diagnosticsmentioning
confidence: 99%